2018
DOI: 10.3846/23450479.2018.1428832
|View full text |Cite
|
Sign up to set email alerts
|

Swimming With Ideas: What Happens to Creativity in the Wake of a Disaster and the Waves of Pro-Social Recovery Behaviour That Follow?

Abstract: Abstract. Creativity that is driven by a need for physical or economic survival, which disasters are likely to inspire, raises the question of whether such creativity fits with conventional theories and perspectives of creativity. In this paper we use the opportunity afforded by the 2010-2013 Christchurch, New Zealand earthquakes to follow and assess the creative practices and responses of a number of groups and individuals. We use in-depth interviews to tease out motivations and read these against a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…The circumstances allowed and supported individuals and groups to take chances. In a post‐disaster setting, it seems that adherence to past norms can waver, leaving a less regulated and recognizable environment in which entrepreneurs can activate ideas and exploit the wealth of opportunities that arise (Cameron et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The circumstances allowed and supported individuals and groups to take chances. In a post‐disaster setting, it seems that adherence to past norms can waver, leaving a less regulated and recognizable environment in which entrepreneurs can activate ideas and exploit the wealth of opportunities that arise (Cameron et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Those who are comfortable on society's fringes, who may even consider themselves ‘outsiders’, are perhaps preadapted for action after a disaster. They are more comfortable than others when things are not ‘normal’ (Cameron et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some crises are experienced at personal level (e.g., the diagnosis of a life-threatening disease), organizational level (e.g., a business facing bankruptcy), and still others are experienced on a societal or global level (e.g., . Although crises can be deeply troubling and anxiety provoking, they can also serve as an important catalyst for creative action and innovative outcomes at and beyond the individual level (Solnit, 2010;Cameron et al, 2018;Cohen and Cromwell, 2020;Leontidou, 2020). Moreover, these creative efforts can occur at individual, grassroots, and broader social levels.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one recent qualitative study of Dutch local governments found considerable evidence of civil service employees implementing creative solutions to solve local problems, such as finding “tailor‐made solutions for citizens” within the context of existing rules and regulations (Kruyen & van Genugten, in press). Another qualitative study documented and analyzed instances of citizens who generated and implemented creative solutions to a myriad of problems following the devastating earthquakes of 2010–2011 in Christchurch, New Zealand—solutions as diverse as a shopping complex in upcycled shipping containers, a bar in a bus, and an automated outdoor dance floor on vacant land (Cameron‐Agnew, Montgomery, Stewart, & Moore, ).…”
mentioning
confidence: 99%